Optimizing Budget Accuracy in the Mining Industry Through Zero-Based Budgeting - Firmansyah Firmansyah; Ahmad Juanda; Driana Leniwati (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study discusses the application of the Zero-Based Budgeting (ZBB) method in the mining industry to improve budget accuracy and operational efficiency. The main objective of this study is to explore how ZBB can help companies plan and manage budgets more effectively, as well as identify potential cost savings that can be achieved through an in-depth analysis of each budget item. The method used in this study is literature analysis, which includes a review of various academic sources and best practices in the application of ZBB in the mining industry. The results of the study indicate that the implementation of ZBB not only optimizes budget accuracy but also increases transparency in the budgeting process, strengthens accountability, and supports better decision making. In addition, this study found that ZBB can encourage a culture of savings and innovation within the organization, which in turn contributes to the sustainability and competitiveness of mining companies in the global market.